RESISTENSI DAN TATANAN PIKIRAN PEREMPUAN DALAM CERITA ANAK TRADISIONAL JAWA TENGAH - , Harjito ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research entitled Resistance and Woman Mindset in the Traditional Children Stories from Central Java. The problems of this research are field